BEYOND NUMBERS: DECODING THE DYNAMICS OF QUALITATIVE ACCOUNTING RESEARCH ACROSS DECADES - Adiningsih, Triana Eva (UI Scholars Hub, 2025)
Background: This study examines the realm of qualitative research in accounting, highlighting its evolving methodologies and thematic emphasis. There has been increasing interest in qualitative methodologies, such as literature reviews, SLRs, archival research, bibliometric studies, and interviews, to explore the complex nature of accounting practices. Methods: This study identifies the principal themes, trends, and prominent authors in qualitative accounting research through a systematic approach that incorporates bibliometric analysis using VOSviewer and a thorough assessment of Scopus-indexed journals. Findings: The findings highlight significant themes, including sustainability, technology, governance, and the impact of global occurrences, such as the COVID-19 pandemic, on accounting practices. The discussion also encompasses challenges in conducting qualitative research, such as obtaining access and maintaining anonymity. Conclusions: This study enhances comprehension of the field’s conceptual framework and guides future research, especially in areas such as blockchain, artificial intelligence, and sustainability accounting. The findings provide essential insights for researchers seeking to address the complexities inherent in modern accounting. Novelty/Originality of this article: The qualitative research currently available either discusses a specific topic or focuses on a particular journal, but none examines the general approach to qualitative research in accounting. This paper aims to address this gap by exploring how qualitative research has been conducted in top-ranked journals, providing readers with insights into qualitative research relevant to the field of accounting.